2022
DOI: 10.3390/ijerph191911845
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Water, Sanitation, and Hygiene for Urban Poor in Low- and Middle-Income Countries during the COVID-19 Pandemic through a Gendered Lens

Abstract: Inadequate water, sanitation, and hygiene (WASH) among urban poor women is a major urban policy concern in low- and middle-income countries (LMICs). There was a paucity of systematic information on WASH among the urban poor during the pandemic. We reviewed the opportunities and challenges faced by the urban poor in LMICs during the COVID-19 pandemic. We used the PRISMA guidelines to conduct a comprehensive search of 11 databases, including MEDLINE, Embase, Web of Science, and CINAHL, between November 2019 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…These findings included perceptions of different countries and income contexts. Other studies that investigated adherence to different nonpharmaceutical measures in different socioeconomic contexts also indicated that government financial support is a determinant for adherence to nonpharmaceutical measures [105,[129][130][131][132][133][134][135][136].…”
Section: Discussionmentioning
confidence: 99%
“…These findings included perceptions of different countries and income contexts. Other studies that investigated adherence to different nonpharmaceutical measures in different socioeconomic contexts also indicated that government financial support is a determinant for adherence to nonpharmaceutical measures [105,[129][130][131][132][133][134][135][136].…”
Section: Discussionmentioning
confidence: 99%